Intervención del trabajo social familiar frente a conflictos familiares afectando la conducta en niño/as en la ciudad de Arenillas - Espinoza Cabrera, Teresa Paulina (My University, 2019)
The present work has as aim “Describe the intervention of the Social Worker inside the familiar area approaching the familiar conflicts and the methodology that it uses in the process to mobilize human and social resources”. To develop the present investigation a bibliographical review was realized in correspondence to the family and the conflicts that threaten the stability of the same one according to Flatteries (2014), Eroles (2001), Giraldo (2014), Martínez, Rodríguez, Días and Kings (2018), Vargas (2014). Of I remind the authors before mentioned they consider to the family as the basic unit of the company, it is the first social area of the human being for the development of the identity of the child and the teenager; where he is formed with the values, beginning and customs that the parents reflect in the diary to live. Nevertheless, the family meets exposed to factors that can give origin to the problems that threaten the balance of the familiar group provoking the conflicts between his members. On having conceived to the family as social system, the Social Work intervenes in the problematics bearing some factors in mind as: socioeconomic, demographic or cultural factors, in agreement to the familiar group. The boarding that realizes the Social Familiar Work is by means of a methodological process named mediation, the same one that looks with the help of a person for neutral third party and the voluntary participation of the involved ones, it could come to a possible solution of the conflict and achieve the social well-being of the persons allowing them to live and to act of a more satisfactory and autonomous form.
El presente trabajo tiene como objetivo “Describir la intervención del Trabajador Social dentro del ámbito familiar abordando los conflictos familiares y la metodología que utiliza en el proceso para movilizar recursos humanos y sociales”. Para desarrollar la presente investigación se realizó una revisión bibliográfica en correspondencia a la familia y los conflictos que amenazan la estabilidad de la misma según Cobas (2014), Eroles (2001), Giraldo (2014), Martínez, Rodríguez, Díaz y Reyes (2018), Vargas (2014). De acuerdo a los autores antes mencionados consideran a la familia como la unidad básica de la sociedad, es el primer ámbito social del ser humano para el desarrollo de la identidad del niño y del adolescente; donde se forma con los valores, principios y costumbres que reflejan los padres en el diario vivir. Sin embargo, la familia se ve expuesta a factores que pueden dar origen a los problemas que amenazan el equilibrio del grupo familiar provocando los conflictos entre sus miembros. Al concebir a la familia como sistema social, el Trabajo Social interviene en la problemática teniendo en cuenta algunos factores como: factores socioeconómicos, demográficos o culturales, de acuerdo al grupo familiar. El abordaje que realiza el Trabajo Social familiar es mediante un proceso metodológico denominado mediación, el mismo que busca con la ayuda de una persona tercero neutral y la participación voluntaria de los involucrados, se pueda llegar a una posible solución del conflicto y lograr el bienestar social de las personas permitiéndoles vivir y actuar de una forma más satisfactoria y autónoma.
Keywords: FAMILIA; MEDIACION; INTERVENCION; CONFLICTO